A Study to Evaluate the Effectiveness of Health Education Regarding Knowledge of Lifestyle Modification during Hypertension among Teaching Professionals Working at Selected Schools of Vadodara - Patel, Sonal; Patel, Bhargavi; Patel, Dhara; Patel, Bhumi (International Journal of Psychosocial Rehabilitation, 2020)
Background of the study: Hypertension is the most common disease in today’s era. In general, high blood pressure-related problems are observed due to a lack of adequate knowledge, the complexity of the diet due to a fast lifestyle, more consumption of alcohol, and obesity. The mortality and morbidity rate is also increasing day by day, as hypertension can cause many related disorders in the human body. Hence, as hypertension has slow and silent pathophysiology, it is also known as “silent killer disease.” In such cases, health education primitive action to make people aware of lifestyle modification during hypertension.Material and method: The research design used in this study was a pre-experimental one-group pre-test post-test design. The sampling technique used for this study was non-probability purposive sampling. The samples were 60 teaching professionals from selected schools in Vadodara city. The tool consists of a sociodemographic tool and structured knowledge questionnaires about lifestyle modification during hypertension The data analysis was planned on the basis of the objectives of the study using descriptive and inferential statistics in consideration with the hypothesis of the research study.Result: This study revealed that knowledge regarding lifestyle modification during hypertension was inadequate, and after the health education program, knowledge regarding lifestyle modification was increased. Data analysis was carried out using descriptive and inferential statistics methods by using SPSS. It was observed that the mean post-test knowledge is significantly higher than the pre-test knowledge.Discussion and conclusion: Blood pressure is the force that a person's blood exerts against the walls of the blood vessels. This pressure depends on the resistance of the blood vessels and how hard the heart has to work. This study was undertaken to assess the effectiveness of a health teaching program regarding lifestyle modification during hypertension. The study involves a one-group pretest-posttest pre-experimental design with a non-probability purposive sampling technique and 60 samples.